Antimicrobial resistance surveillance in the South African private sector report for 2016. Issue 4 (2nd October 2018) - Perovic, Olga; Ismail, Husna; Van Schalkwyk, Erika; Lowman, Warren; Prentice, Elizabeth; Senekal, Marthinus; Govind, Chetna N
Abstract : Aim: The relevance of surveillance for antimicrobial resistance is increasingly recognised in the light of a global action plan to combat resistance. This report presents antimicrobial susceptibility testing on ESKAPE pathogens from private sector laboratories in South Africa for 2016. Methods: Antimicrobial susceptibility testing (AST) performed on ESKAPE organisms ( Enterococcus faecium, Enterococcus faecalis, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, Enterobacter cloacae and Escherichia coli ) isolated from blood cultures at four private pathology laboratories in 2016 were analysed. Analysis and reporting of data were done via a uniform platform created by the NICD for national AST data. Results: AST were reported on 9 029 ESKAPE organisms including 58% Enterobacteriaceae, 28% Gram-positive bacteria and 14% Gram-negative bacteria and drug-bug combination was performed following the Global Antimicrobial Surveillance System (GLASS) guidelines by the World Health Organization. Conclusions: The most important resistance to address is a high level of ESBL in Enterobacteriaceae, which necessitates the use of carbapenems for treatment. Resistance to carbapenems is recorded in this report but not confirmation of genes by genotypic methods. During this period, no increase in vancomycin-resistant Enterococci was observed.